Clinician testimony in suicide litigation: A cause to be uneasy. (3rd June 2019) - Simpson, Skip; Reid, William H.
Abstract : This is an illustrative article rather than a research study. We offer opinions and recommendations about what we view as unfortunate clinician testimony in suicide‐related malpractice cases, testimony that – inadvertently or not – supports or encourages inadequate care of suicidal patients. The principles apply to both psychiatrists and non‐psychiatrists, although the former appear more often in our work. We particularly consider the roles and testimony, in court or at deposition, of psychiatrists, whether as defendants, expert witnesses, or fact witnesses. We cite examples of what we view as poor, disingenuous, dishonest and even dangerous testimony that we believe moves the profession toward unsafe patient care. The examples illustrate what we (and sometimes others) describe as normalization of deviance, pre‐suit puffery, self‐serving defendant testimony, expert pride supplanting testimonial responsibility, expert arrogance, expert parroting of attorney suggestions, witness ignorance and avoiding facts, unconscious expert bias, inexperience thwarting justice, misleading use of terms such as "predictability, " and expert witnesses who lack the direct‐care experience that jurisdictions often require in order to opine about defendant clinicians' day‐to‐day patient care. The examples often reveal concerns beyond the category chosen, and should not be expected to convey all of the facts of a particular case.